Cigarette Smoking Disrupts Sperm Nuclear Maturation, Epigenetic Regulation, and CatSper-Mediated Calcium Signaling - Tulay Irez; Tugba Elgun; Goksun Demirel; Enver Ciraci; Emre Salabas (Gynecology Obstetrics & Reproductive Medicine, 2026)
OBJECTIVE: The CatSper (cation channel of sperm) channel is the principal pH-sensitive and low-voltage-activated cation channel that regulates Ca²⁺ influx required for sperm hyperactivation. Exposure to cigarette smoke is known to affect semen parameters and sperm DNA integrity adversely. This study aimed to investigate the effects of cigarette smoking on semen analysis results, sperm DNA fragmentation, chromatin condensation, global DNA methylation, and CatSper4 immunoreactivity. STUDY DESIGN: In this case-control study, 50 men who presented for infertility evaluation between November 2019 and November 2021 were divided into two groups: non-smokers (n=25) and those who smoked approximately one pack of cigarettes per day (n=25). Twenty of these cases were normospermic and 30 oligospermic. Semen analysis was performed according to the World Health Organization 2010 criteria. Sperm DNA fragmentation was assessed by acridine orange staining, chromatin condensation by aniline blue staining, global DNA methylation by 5-methylcytosine (5-mC) ELISA assay, and CatSper4 expression by immunofluorescence staining. RESULTS: In normospermic men, no statistically significant smoking-related differences were observed in conventional semen parameters, DNA fragmentation, chromatin condensation, or CatSper4 positivity. In oligospermic men, smoking was associated with significantly higher sperm DNA fragmentation and significantly lower chromatin condensation and CatSper4 positivity. In contrast, sperm concentration, motility, and normal morphology did not differ significantly between smokers and non-smokers. Global DNA methylation levels were significantly higher in smokers than in non-smokers (1.81±0.52 vs. 1.11±0.35, respectively; p=0.0012). CONCLUSION: Cigarette smoking may impair male fertility potential primarily through alterations in sperm DNA integrity, chromatin maturation, global DNA methylation, and CatSper4-related calcium signaling, particularly in oligospermic men. Larger-scale studies using individual-level datasets are required to confirm these findings and clarify their clinical significance.